Continuous-Flow Synthesis of 2H-Azirines and Their Diastereoselective Transformation to Aziridines - Baumann, Marcus; Baxendale, Ian R. (Synlett, 2016)
Using continuous-flow techniques, a small collection of 2H-azirines was prepared from oxime precursors via mesylation and base-promoted cyclisation. The 2H-azirines were either isolated after in-line purification or derivatised into a selection of 2-substituted aziridines through a telescoped reaction sequence involving nitrile, trifluoromethyl, or hydride nucleophilic addition. Importantly, these 2-substituted aziridines were produced with high cis diastereoselectivity providing access to small chiral heterocyclic entities that hold promise for medicinal chemistry programs because of their druglike features.
Keywords: flow synthesis; heterocycles; azirine; aziridine; microreactor; monolith; in-line purification